Lithium manganese iron phosphate battery with ultrahigh power, high specific energy, wide temperature range and high safety and preparation method thereof
By using spherical nanoscale spherical nanometer-level lithium manganese phosphate with high ferromanganese ratio and isotropic small-particle-sized negative electrode material in lithium manganese phosphate batteries, combined with a high conductive agent network and an optimized electrolyte, the battery's shortcomings in high power, wide temperature domain and high safety are solved, and the effect of high specific energy density and long life is achieved.
Patent Information
- Application Number
- CN202411849610.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
Existing lithium manganese ferrophosphate batteries have shortcomings in high power, wide temperature domain and high safety, especially in high-rate charging and discharging and low-temperature cold start.
A spherical nanoscale lithium manganese phosphate with high ferromanganese ratio is used as the positive electrode active material, and combined with isotropic small-particle-size negative electrode material, a high conductive agent network combined with "point-line-surface" is constructed, and an electrolyte with high conductivity and low viscosity is used, and ultra-high power density and high specific energy density are achieved through optimized process design.
The battery has achieved a balance of high power density, wide temperature range and high safety, has the ability to continuously discharge 30C, and performs well under cold start-up and high temperature use conditions of -40℃, and has passed the GJB2374A-2013 safety test.
Smart Images

Figure BDA0005190207810000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of power lithium batteries, and in particular relates to an ultra-high power, wide temperature range and high safety lithium manganese iron phosphate battery and a preparation method thereof. Background Art
[0002] In view of the sustainable development of resources, the increasingly prominent lithium battery safety issues and the growing demand for operating conditions, batteries in the consumer, power and energy storage fields must not only improve the safety and electrical performance of batteries, but also reduce excessive dependence on rare metals such as nickel and cobalt. For example, vehicles and drones have an increasing demand for energy storage products with technical indicators such as high safety, high energy density and high power density (double high type) and wide temperature range. The mainstream ternary (NCM) large-capacity batteries have poor safety and poor high-temperature performance, while the lithium iron phosphate (LFP) monomer specific energy is close to the limit (200Wh / kg, especially the rate performance is poor at high specific energy density), poor low-temperature performance and low voltage platform. The above-mentioned technical and product shortcomings cannot meet the comprehensive technical requirements of vehicles, drones and special for high safety, high specific energy, high rate and wide temperature range. Based on this, from the perspective of technological development, it is urgent to develop new technologies and products that integrate "high safety, high power, high specific energy, wide temperature range, long life and low cost". In this context, lithium manganese iron phosphate (LMFP) is a new system. Its products increase the charging voltage from 3.2V of LFP to 4.1V. The theoretical energy density of LMFP battery increases by 15-20%, and the low-temperature performance increases by 5-8%. Compared with NCM ternary materials, the inherent olivine structure stability of LMFP is higher than the layered structure of NCM ternary materials, so its battery safety is also much higher than that of ternary batteries. The safety performance is better than NCM. Iron, manganese and phosphorus are all elements with relatively high abundance in the earth's crust. LMFP has low dependence on rare metals and obvious cost advantages. Therefore, lithium manganese iron phosphate has better technical and product advantages.
[0003] In view of the characteristics of small particles and high specific surface area of lithium manganese iron phosphate, it is easy to agglomerate when forming a slurry, which is not conducive to the subsequent coating process. The patent (CN 117855426A) discloses a dispersion and slurry process for lithium manganese iron phosphate batteries. It mainly adds lithium manganese iron phosphate to the conductive slurry, and then adds a dispersant and lithium nickel oxide for high-speed dispersion, and finally obtains a positive electrode slurry with a solid content of 58% to 60%. The invention proposes that the step-by-step addition of the conductive agent is conducive to the formation of a uniformly dispersed conductive slurry, and then constructs an efficient three-dimensional conductive network. The slurry has good fluidity and stability and excellent dispersion performance. However, the invention is limited to the slurry production process based on lithium manganese iron phosphate, and its positive electrode formula types and proportions are not suitable for the design of high-energy-density and high-power dual-high and wide-temperature range batteries. CN 117691183 A discloses an electrolyte for a lithium manganese iron phosphate battery, wherein the key to the electrolyte is an additive A containing boron, nitrogen and carbon aromatic compounds, which can form an interface film with high conductivity at the electrode interface, and can also remove HF and inhibit the dissolution of manganese ions. In the embodiments disclosed in the invention, although it is proved that additive A can improve the cycle performance and rate performance of the lithium manganese iron phosphate battery, the capacity retention rate of the lithium manganese iron phosphate battery after 500 cycles is 89% to 94%, the DC internal resistance increases by 13% to 23%, and the 2C rate discharge capacity is 81% to 86% of the 0.33C discharge capacity. For the technical requirements of the emergency / starting power supply of unmanned aerial vehicles or vehicles for dual high power supplies, the above-mentioned lithium manganese iron phosphate battery obviously cannot meet its 20C or even 30C sustained rate discharge requirements.
[0004] CN 117276471 A discloses a high-safety and high-specific-energy lithium iron manganese phosphate battery, the active material of which is a positive electrode sheet coated with lithium iron manganese phosphate, lithium manganese phosphate and lithium iron phosphate on the surface of an aluminum foil current collector, and a negative electrode made of graphite. The capacity retention rates of a 4000mAh battery based on the positive and negative electrodes for 500 and 1000 cycles are 98% and 91% respectively, and the battery has passed tests such as acupuncture, overcharging and thermal shock. The positive electrode of this technical solution uses a composite positive electrode material, not a pure lithium iron manganese phosphate material, and does not reflect the specific energy of the battery. In fact, the lithium iron manganese phosphate material exists in the form of a solid solution with a certain manganese-iron ratio, rather than a simple mechanical physical mixture of lithium manganese phosphate and lithium iron phosphate. This technical solution does not yet mention the rate and high-temperature performance of the battery.
[0005] CN 117276471 A discloses a high-safety and high-specific-energy lithium iron phosphate battery, which aims to provide a lithium iron phosphate battery with a low DC impedance level and good low-temperature performance for high-rate charge and discharge. In the embodiment of the technical scheme, the low-temperature capacity of the battery of lithium iron phosphate mixed with ternary, lithium iron phosphate mixed with lithium iron phosphate, lithium iron phosphate mixed with lithium cobalt oxide and pure lithium iron phosphate is provided respectively, and the order is lithium iron phosphate mixed with lithium cobalt oxide> lithium iron phosphate mixed with ternary> lithium iron phosphate mixed with lithium iron phosphate> lithium iron phosphate, and the higher the content of ternary materials, the better the low-temperature performance. The low-temperature capacity of the battery based on pure lithium iron phosphate at -10°C is 55% to 70% of the capacity at 25°C. The technical scheme does not yet mention the rate performance, high-temperature performance and specific energy of the battery. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned technology and provide an ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery and a preparation method thereof, which achieves continuous 30C continuous discharge and takes into account high specific energy density; at the same time, it has -40℃ cold start discharge requirements and high temperature operating conditions; and passes the GJB2374A-2013 safety test requirements.
[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: an ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery, including a positive electrode sheet, a negative electrode sheet, a diaphragm, an electrolyte, an aluminum plastic shell and a pole ear, the positive electrode sheet and the negative electrode sheet are respectively located on both sides of the diaphragm to form a laminated structure, the positive electrode sheet includes a positive electrode collector and a positive electrode mixture, the positive electrode collector is a carbon-coated aluminum foil with a thickness of 8 to 12 μm, the positive electrode mixture includes a positive electrode active material, a positive electrode conductive agent, a positive electrode dispersant and a positive electrode binder, the positive electrode active material is a carbon-coated spherical nano-scale lithium manganese iron phosphate, the manganese / iron molar ratio is 6 / 4 or 7 / 3, and the particle size is 0.5 μm<D 50 <1.5μm, carbon coating layer 3~5nm; the negative electrode sheet includes a negative electrode current collector and a negative electrode mixture, the negative electrode mixture includes a negative electrode active material, a negative electrode conductive agent, a negative electrode dispersant and a negative electrode binder, the negative electrode active material adopts at least one of isotropic graphite, soft carbon, hard carbon, silicon carbon or silicon oxygen, and the particle size is 2μm<D 50 <6μm; the diaphragm adopts a ceramic-coated polyethylene diaphragm or a ceramic-coated polypropylene diaphragm with a thickness of 9 to 16μm; the electrolyte includes a lithium salt, a solvent and an additive, and the electrolyte conductivity at 25°C is above 10.5mS / cm.
[0008] The positive electrode mixture comprises 95% to 95.6% of a positive electrode active material, 2.5% to 3% of a positive electrode conductor, 0.1% to 0.3% of a positive electrode dispersant and 1.5% to 2.0% of a positive electrode binder by weight percentage.
[0009] The negative electrode mixture comprises, by weight percentage, 94.8% to 95.2% of a negative electrode active material, 2.0% to 3.0% of a negative electrode conductor, 0.7% to 1.5% of a negative electrode dispersant and 1.5% to 2.5% of a negative electrode binder.
[0010] The lithium salt in the electrolyte is at least two of lithium bis(fluorosulfonyl)imide LiFSI, lithium hexafluorophosphate LiPF6 and lithium bis(trifluoromethylsulfonyl)imide LiTFSI, with a mass concentration of 11% to 22%; the solvent is at least two of vinyl carbonate EC, ethyl methyl carbonate EMC, propylene carbonate PC, ethyl propionate EP, methyl propionate MP and diethyl carbonate DEC, with a mass concentration of 72% to 82%; the additives include at least four of vinyl carbonate VC, propylene sulfite PS, fluoroethylene carbonate FEC, vinyl sulfate DTD, lithium difluorophosphate LiPO2F2, lithium tetrafluoroborate LiBF4, lithium bis(fluorooxalate)borate LiODFB and lithium bis(oxalate)borate LiBOB, with a mass concentration of 5% to 10%.
[0011] The positive electrode current collector is a carbon-coated aluminum foil, wherein the base foil thickness is 7-10 μm and the carbon-coated layer thickness is 1-2 μm; the negative electrode current collector is an electrolytic copper foil, wherein the thickness of the electrolytic copper foil is 4.5-8 μm.
[0012] The positive electrode conductive agent is at least one of carbon black, Ketjen black or carbon nanotubes, the dispersant is at least one of polyvinyl pyrrolidone and polydiphenyl butylene ester, and the positive electrode binder is polyvinylidene fluoride.
[0013] The positive electrode sheet is coated on both sides, wherein the single-side coating density of the positive electrode mixture is 7.1 to 12.5 mg / cm 2 The negative electrode sheet is coated on both sides, and the single-sided coating density of the negative electrode mixture is 3.6 to 7.2 mg / cm 2 .
[0014] The negative electrode conductive agent is at least one of graphene, carbon black, Ketjen black or carbon nanotubes, the negative electrode dispersant is sodium carboxymethyl cellulose CMC, and the negative electrode binder is styrene-butadiene rubber SBR.
[0015] The thickness of the aluminum-plastic shell is 0.113-0.153 mm, the size of the positive electrode tab is 25-60 mm wide and 0.3-0.4 mm thick, and the size of the negative electrode tab is 25-60 mm wide and 0.2-0.3 mm thick.
[0016] The method for preparing the above-mentioned ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery comprises the following steps:
[0017] 1) The positive electrode active material, conductive agent, binder and dispersant are made into a uniform and stable slurry according to the homogenization process, the slurry is coated on the positive electrode collector, dried at a certain temperature and wind speed, and then rolled before entering the subsequent process; the negative electrode active material, conductive agent, binder and dispersant are made into a uniform and stable slurry according to the homogenization process, the slurry is coated on the negative electrode collector, dried at a certain temperature and wind speed, and stored before entering the next process;
[0018] 2) Cut the rolled positive and negative electrode sheets into a certain width respectively, and stack them together in the order of separator, negative electrode sheet, separator, and positive electrode sheet to form a stacked electrode group, which is then short-circuited and X-ray aligned;
[0019] 3) The qualified pole group and the pole ear are welded together, loaded into an aluminum plastic shell, and pre-packaged on the top in turn. After the packaging effect is checked, the qualified battery cell enters a vacuum high-temperature oven for several hours to remove the trace moisture remaining in the battery. The drying temperature is 80-95°C, the drying time is 24-36 hours, and the vacuum degree is -100kPa;
[0020] 4) Perform a short circuit test on the dried battery, and test the moisture content of the positive electrode, negative electrode and diaphragm respectively; inject a certain amount of electrolyte into the battery with qualified moisture, with a net liquid volume of 4.2-5.3 mg / Ah, and let it stand for 4-12 hours;
[0021] 5) After the standing is completed, the pre-formation is performed first, and the battery is activated by charging with a small rate current, the charging current is 0.05C-0.2C, and the charging time is 30-60 minutes. At the same time, the gas generated during the battery activation process is discharged to form a compact and uniform solid electrolyte membrane;
[0022] 6) After pre-forming, exhaust, sealing and forming are carried out. Formation process: the battery is charged and discharged 1 to 3 times to fully activate it, the charge and discharge current is 0.2C to 0.5C, and the charge and discharge voltage is 2.5 to 4.3V;
[0023] 7) After the formation, the aging process begins. The aging temperature is 35-40°C and the aging time is 7-10 days.
[0024] Beneficial effects of the invention: Compared with the prior art, the invention takes into account ultra-high power density, high specific energy density, high safety and wide temperature application range. The invention improves the battery power density in all directions from the optimization of materials, pole piece design and manufacturing process, that is, reduces the charge transfer impedance, improves the lithium ion migration diffusion coefficient and electronic conductivity of the material, and takes into account its specific energy, cycle life, high and low temperature performance and safety performance. Specifically, from the material level, spherical nano-scale lithium manganese iron phosphate with a high manganese to iron ratio and isotropic small-particle negative electrode materials (including coating and doping of positive and negative electrode materials) are selected, and a high-conductivity agent combined with "point-line-surface" is used to construct long and short-range conductive networks, high-permeability thin diaphragms and high-conductivity, low-viscosity, wide-temperature range electrolytes, which essentially improve the migration rate of electrons and lithium ions and reduce the internal resistance and polarization of the battery, especially at high rates and low temperatures; from the process level, positive and negative electrode sheets with ultra-low coating amounts are designed and manufactured to shorten the lithium ion diffusion path, and a wide pole ear stacked soft package structure is used to reduce the heat generated by high-rate charging and discharging, providing a lithium-ion battery with ultra-high power charging and discharging, long life and safety. DETAILED DESCRIPTION
[0025] In order to more clearly understand the above-mentioned purpose, technical features and product advantages of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other. In the following description, many specific details are set forth in order to fully understand the present invention, and the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0026] The invention discloses an ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery, comprising a positive electrode sheet, a negative electrode sheet, a diaphragm, an electrolyte, an aluminum plastic shell and a pole ear, wherein the positive electrode sheet and the negative electrode sheet are respectively located on both sides of the diaphragm to form a laminated structure, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode mixture, wherein the positive electrode current collector is a carbon-coated aluminum foil with a thickness of 8 to 12 μm, wherein the positive electrode mixture comprises a positive electrode active material, a positive electrode conductive agent, a positive electrode dispersant and a positive electrode binder, wherein the positive electrode active material is a carbon-coated spherical nano-scale lithium manganese iron phosphate, wherein the manganese / iron molar ratio is 6 / 4 or 7 / 3, and the particle size is 0.5 μm<D 50<1.5μm, carbon coating layer 3~5nm; the negative electrode sheet includes a negative electrode current collector and a negative electrode mixture, the negative electrode mixture includes a negative electrode active material, a negative electrode conductive agent, a negative electrode dispersant and a negative electrode binder, the negative electrode active material adopts at least one of isotropic graphite, soft carbon, hard carbon, silicon carbon or silicon oxygen, and the particle size is 2μm<D 50 <6μm; the diaphragm adopts a ceramic-coated polyethylene diaphragm or a ceramic-coated polypropylene diaphragm with a thickness of 9 to 16μm; the electrolyte includes a lithium salt, a solvent and an additive, and the electrolyte conductivity at 25°C is above 10.5mS / cm.
[0027] The positive electrode mixture comprises 95% to 95.6% of a positive electrode active material, 2.5% to 3% of a positive electrode conductor, 0.1% to 0.3% of a positive electrode dispersant and 1.5% to 2.0% of a positive electrode binder by weight percentage.
[0028] The negative electrode mixture comprises, by weight percentage, 94.8% to 95.2% of a negative electrode active material, 2.0% to 3.0% of a negative electrode conductor, 0.7% to 1.5% of a negative electrode dispersant and 1.5% to 2.5% of a negative electrode binder.
[0029] The lithium salt in the electrolyte is at least two of lithium bis(fluorosulfonyl)imide LiFSI, lithium hexafluorophosphate LiPF6 and lithium bis(trifluoromethylsulfonyl)imide LiTFSI, with a mass concentration of 11% to 22%; the solvent is at least two of vinyl carbonate EC, ethyl methyl carbonate EMC, propylene carbonate PC, ethyl propionate EP, methyl propionate MP and diethyl carbonate DEC, with a mass concentration of 72% to 82%; the additives include at least four of vinyl carbonate VC, propylene sulfite PS, fluoroethylene carbonate FEC, vinyl sulfate DTD, lithium difluorophosphate LiPO2F2, lithium tetrafluoroborate LiBF4, lithium bis(fluorooxalate)borate LiODFB and lithium bis(oxalate)borate LiBOB, with a mass concentration of 5% to 10%.
[0030] The positive electrode current collector is a carbon-coated aluminum foil, wherein the base foil thickness is 7-10 μm and the carbon-coated layer thickness is 1-2 μm; the negative electrode current collector is an electrolytic copper foil, wherein the thickness of the electrolytic copper foil is 4.5-8 μm.
[0031] The positive electrode conductive agent is at least one of carbon black, Ketjen black or carbon nanotubes, the dispersant is at least one of polyvinyl pyrrolidone and polydiphenyl butylene ester, and the positive electrode binder is polyvinylidene fluoride.
[0032] The positive electrode sheet is coated on both sides, wherein the single-side coating density of the positive electrode mixture is 7.1 to 12.5 mg / cm 2 The negative electrode sheet is coated on both sides, and the single-sided coating density of the negative electrode mixture is 3.6 to 7.2 mg / cm2 .
[0033] The negative electrode conductive agent is at least one of graphene, carbon black, Ketjen black or carbon nanotubes, the negative electrode dispersant is sodium carboxymethyl cellulose CMC, and the negative electrode binder is styrene-butadiene rubber SBR.
[0034] The thickness of the aluminum-plastic shell is 0.113-0.153 mm, the size of the positive electrode tab is 25-60 mm wide and 0.3-0.4 mm thick, and the size of the negative electrode tab is 25-60 mm wide and 0.2-0.3 mm thick.
[0035] The method for preparing the above-mentioned ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery comprises the following steps:
[0036] 1) The positive electrode active material, conductive agent, binder and dispersant are made into a uniform and stable slurry according to the homogenization process, the slurry is coated on the positive electrode collector, dried at a certain temperature and wind speed, and then rolled before entering the subsequent process; the negative electrode active material, conductive agent, binder and dispersant are made into a uniform and stable slurry according to the homogenization process, the slurry is coated on the negative electrode collector, dried at a certain temperature and wind speed, and stored before entering the next process;
[0037] 2) Cut the rolled positive and negative electrode sheets into a certain width respectively, and stack them together in the order of separator, negative electrode sheet, separator, and positive electrode sheet to form a stacked electrode group, which is then short-circuited and X-ray aligned;
[0038] 3) The qualified pole group and the pole ear are welded together, loaded into an aluminum plastic shell, and pre-packaged on the top in turn. After the packaging effect is checked, the qualified battery cell enters a vacuum high-temperature oven for several hours to remove the trace moisture remaining in the battery. The drying temperature is 80-95°C, the drying time is 24-36 hours, and the vacuum degree is -100kPa;
[0039] 4) Perform a short circuit test on the dried battery, and test the moisture content of the positive electrode, negative electrode and diaphragm respectively; inject a certain amount of electrolyte into the battery with qualified moisture, with a net liquid volume of 4.2-5.3 mg / Ah, and let it stand for 4-12 hours;
[0040] 5) After the standing is completed, the pre-formation is performed first, and the battery is activated by charging with a small rate current, the charging current is 0.05C-0.2C, and the charging time is 30-60 minutes. At the same time, the gas generated during the battery activation process is discharged to form a compact and uniform solid electrolyte membrane;
[0041] 6) After pre-forming, exhaust, sealing and forming are carried out. Formation process: the battery is charged and discharged 1 to 3 times to fully activate it. The charge and discharge current is 0.2C to 0.5C, and the charge and discharge voltage is 2.5 to 4.3V;
[0042] 7) After the formation, the aging process begins. The aging temperature is 35-40°C and the aging time is 7-10 days.
[0043] The preferred embodiment of the present invention is that the positive electrode active material is carbon-coated spherical nano-scale lithium manganese iron phosphate, the manganese / iron molar ratio is 6 / 4 or 7 / 3, the particle size is 0.5μm<D50<1.5μm, and the carbon coating layer is 3-5nm; the positive electrode conductive agent is one or a mixture of two or more of carbon black, Ketjen black or carbon nanotubes, the dispersant is one or a mixture of two of polyvinyl pyrrolidone and polydiphenyl butyl ester, and the positive electrode binder is polyvinylidene fluoride. The positive electrode sheet is double-sided coated, and the single-sided coating surface density of the positive electrode mixture is 7.1-12.5mg / cm 2 .
[0044] The preferred embodiment of the present invention is that the negative electrode active material is at least one of isotropic graphite, soft carbon, hard carbon, silicon carbon or silicon oxygen, and the particle size is 2μm<D50<6μm; the negative electrode conductive agent is one or a mixture of two or more of carbon black, Ketjen black or carbon nanotubes (including single-walled carbon nanotubes); the negative electrode dispersant is sodium carboxymethyl cellulose (CMC); the negative electrode binder is styrene butadiene rubber (SBR). The negative electrode sheet is double-sided coated, and the single-sided coating surface density of the negative electrode mixture is 3.6-7.2 mg / cm 2 .
[0045] The preferred solution of the present invention is that the diaphragm is a single-sided ceramic coating diaphragm with a thickness of 16 μm and a porosity of 42%.
[0046] A preferred embodiment of the present invention is that the electrolyte includes a lithium salt, a solvent and various additives, wherein the lithium salt is at least two of lithium bis(fluorosulfonyl)imide LiFSI, lithium hexafluorophosphate LiPF6 and lithium bis(trifluoromethylsulfonyl)imide LiTFSI, with a mass concentration of 13% to 24%; the solvent is at least three of propylene carbonate PC, ethyl methyl carbonate EMC, ethylene carbonate EC, ethyl propionate EP, methyl propionate MP and diethyl carbonate DEC, with a mass concentration of 70% to 80%; the additives include at least four of vinylene carbonate VC, propylene sulfite PS, fluoroethylene carbonate FEC, vinyl sulfate DTD, lithium difluorophosphate LiPO2F2, lithium tetrafluoroborate LiBF4, lithium bis(fluorooxalate)borate LiODFB and lithium bis(oxalate)borate LiBOB, with a mass concentration of 5% to 10%. Specifically, the weight concentration of the solvent is 10% to 11% of ethylene carbonate EC, 20% to 22% of ethyl methyl carbonate EMC, 20% to 32% of ethyl propionate EP, 15% to 20% of methyl propionate MP, and 3% to 4% of propylene carbonate PC; the additives are 1% to 1.5% of vinylene carbonate VC, 0.5% to 1.0% of propylene sulfite PS, 1.5% to 2% of fluoroethylene carbonate FEC, 1.0% to 1.5% of vinyl sulfate DTD, 0.5% to 1% of lithium difluorophosphate LiPO2F2, 0.4% to 0.6% of lithium bis(fluorooxalate)borate LiODFB, and 0.3% to 0.5% of lithium bis(oxalate)borate LiBOB. The conductivity of the electrolyte at 25°C is above 10.5 mS / cm.
[0047] A preferred embodiment of the present invention is that the battery shell is made of aluminum-plastic material to take into account the battery energy density. The thickness of the battery aluminum-plastic shell is 0.153mm, the positive electrode ear size is 25mm or 50mm wide and 0.4mm thick, and the negative electrode ear size is 25mm or 50mm wide and 0.4mm thick. The positive and negative ends of the electrode group are respectively welded to two pins.
[0048] The present invention is further described in detail below with reference to specific implementation examples.
[0049] Embodiment 1:
[0050] (1) According to the weight percentage, the positive electrode slurry was prepared by mixing 94.5% lithium manganese iron phosphate (manganese iron molar ratio 6 / 4) + 3.4% positive electrode conductive agent (carbon black and carbon nanotubes) + 0.1% positive electrode dispersant YTF303 + 2.0% positive electrode binder PVDF. The positive electrode slurry with moderate solid content and viscosity was coated on the carbon-coated aluminum foil. The single-sided coating surface density of the positive electrode was 11.5 mg / cm 2 , then dried, rolled and cut, and temporarily stored for lamination.
[0051] (2) According to the weight percentage, the negative electrode slurry is prepared by mixing the active material graphite of 95% + the negative electrode conductive agent carbon black of 2.0% + the negative electrode dispersant CMC of 1.2% + the negative electrode binder styrene butadiene rubber formula. The positive electrode slurry with moderate solid content and viscosity is coated on the electrolytic copper foil. The negative electrode single-side coating surface density is 4.6 mg / cm 2 , then dried, rolled and sheared, and temporarily stored for lamination.
[0052] (3) The positive and negative electrodes and the 16 μm ceramic separator in (1) and (2) are stacked in the order of separator, negative electrode, separator, and positive electrode, wherein the positive electrode has 32 layers, the separator has 68 layers, and the negative electrode has 33 layers. The stacked electrode group is welded to the electrode tab, and then placed in a shell, sealed on the top and side, and dried.
[0053] (4) The batteries dried and qualified in (3) are injected with electrolyte at a rate of 3.4 g / Ah. The electrolyte comprises a lithium salt, a solvent and various additives, wherein the lithium salt is 11% lithium hexafluorophosphate LiPF6, 4.5% lithium bis(fluorosulfonyl)imide LiFSI, the solvent is 10% ethylene carbonate EC, 3% propylene carbonate PC, 20% ethyl methyl carbonate EMC, 25% ethyl propionate EP, 20% methyl propionate MP; the additives are 1.8% fluoroethylene carbonate FEC, 1.3% vinylene carbonate VC%, 1% vinyl sulfate DTD, 0.6% lithium difluorophosphate LiPO2F2 and 0.6% propylene sulfite PS, 0.4% lithium bis(fluorooxalate)borate LiODFB and 0.4% lithium bis(oxalate)borate LiBOB.
[0054] (5) After standing for 8 hours, pre-forming is performed. The charging current is 0.05C, charging for 10 minutes, the charging current is 0.1C, charging for 20 minutes, and the charging current is 0.2C, charging for 30 minutes. After that, degas and sealing are performed. The formation format is:
[0055] a. Charge to 4.30V at 0.25C constant current and constant voltage;
[0056] b. Sleep for 30 minutes;
[0057] c. 0.5C discharge to 2.50V;
[0058] d. Repeat steps a to c twice;
[0059] e. 0.25C charging for 72 minutes.
[0060] (5) The battery in (4) was aged at 30±2°C for 7 days.
[0061] Embodiment 2:
[0062] (1) According to the weight percentage, the positive electrode slurry was prepared by mixing 94.5% lithium manganese iron phosphate (manganese iron molar ratio 6 / 4) + 3.4% positive electrode conductive agent (carbon black and carbon nanotubes) + 0.1% positive electrode dispersant YTF303 + 2.0% positive electrode binder PVDF. The positive electrode slurry with moderate solid content and viscosity was coated on the carbon-coated aluminum foil. The single-sided coating surface density of the positive electrode was 7.1 mg / cm 2 , then dried, rolled and cut, and temporarily stored for lamination.
[0063] (2) According to the weight percentage, the negative electrode slurry is prepared by mixing the active material graphite of 95% + the negative electrode conductive agent carbon black of 2.0% + the negative electrode dispersant CMC of 1.2% + the negative electrode binder styrene butadiene rubber formula. The positive electrode slurry with moderate solid content and viscosity is coated on the electrolytic copper foil. The negative electrode single-side coating surface density is 4.2 mg / cm 2 , then dried, rolled and sheared, and temporarily stored for lamination.
[0064] (3) The positive and negative electrodes and the 16 μm ceramic separator in (1) and (2) are stacked in the order of separator, negative electrode, separator, and positive electrode, wherein the positive electrode has 32 layers, the separator has 68 layers, and the negative electrode has 33 layers. The stacked electrode group is welded to the electrode tab, and then placed in a shell, sealed on the top and side, and dried.
[0065] (4) The batteries dried and qualified in (3) are injected with electrolyte at a rate of 3.4 g / Ah. The electrolyte comprises a lithium salt, a solvent and various additives, wherein the lithium salt is 11% lithium hexafluorophosphate LiPF6, 4.5% lithium bis(fluorosulfonyl)imide LiFSI, the solvent is 10% ethylene carbonate EC, 3% propylene carbonate PC, 20% ethyl methyl carbonate EMC, 25% ethyl propionate EP, 20% methyl propionate MP; the additives are 1.8% fluoroethylene carbonate FEC, 1.3% vinylene carbonate VC%, 1% vinyl sulfate DTD, 0.6% lithium difluorophosphate LiPO2F2 and 0.6% propylene sulfite PS, 0.4% lithium bis(fluorooxalate)borate LiODFB and 0.4% lithium bis(oxalate)borate LiBOB.
[0066] (5) After standing for 8 hours, pre-forming is performed. The charging current is 0.05C, charging for 10 minutes, the charging current is 0.1C, charging for 20 minutes, and the charging current is 0.2C, charging for 30 minutes. After that, degas and sealing are performed. The formation format is:
[0067] a. Charge to 4.30V at 0.25C constant current and constant voltage;
[0068] b. Sleep for 30 minutes;
[0069] c. 0.5C discharge to 2.50V;
[0070] d. Repeat steps a to c twice;
[0071] e. 0.25C charging for 72 minutes.
[0072] 5) The battery in (4) was aged in an environment of 30±2°C for 7 days.
[0073] Embodiment 3:
[0074] (1) According to the weight percentage, the positive electrode slurry was prepared by mixing 94.5% lithium manganese iron phosphate (manganese iron molar ratio 6 / 4) + 3.4% positive electrode conductive agent (carbon black and carbon nanotubes) + 0.1% positive electrode dispersant YTF303 + 2.0% positive electrode binder PVDF. The positive electrode slurry with moderate solid content and viscosity was coated on the carbon-coated aluminum foil. The single-sided coating surface density of the positive electrode was 7.1 mg / cm 2 , then dried, rolled and cut, and temporarily stored for lamination.
[0075] (2) According to the weight percentage, the negative electrode slurry is prepared by mixing the active material graphite of 95% + the negative electrode conductive agent carbon black of 2.0% + the negative electrode dispersant CMC of 1.2% + the negative electrode binder styrene butadiene rubber formula. The positive electrode slurry with moderate solid content and viscosity is coated on the electrolytic copper foil. The negative electrode single-side coating surface density is 4.2 mg / cm 2 , then dried, rolled and sheared, and temporarily stored for lamination.
[0076] (3) The positive and negative electrodes and the 16 μm ceramic separator in (1) and (2) are stacked in the order of separator, negative electrode, separator, and positive electrode, wherein the positive electrode has 32 layers, the separator has 68 layers, and the negative electrode has 33 layers. The stacked electrode group is welded to the electrode tab, and then placed in a shell, sealed on the top and side, and dried.
[0077] (4) The batteries dried and qualified in (3) are injected with electrolyte at a rate of 3.4 g / Ah. The electrolyte comprises a lithium salt, a solvent and various additives, wherein the lithium salt comprises 11% lithium hexafluorophosphate LiPF6, 4.5% lithium bis(fluorosulfonyl)imide LiFSI, the solvent comprises 10% ethylene carbonate EC, 3% propylene carbonate PC, 20% ethyl methyl carbonate EMC, and 45% ethyl propionate EP; the additives comprise 1.8% fluoroethylene carbonate FEC, 1.3% vinylene carbonate VC%, 1% vinyl sulfate DTD, 0.6% lithium difluorophosphate LiPO2F2, 0.6% propylene sulfite PS, 0.4% lithium bis(fluorooxalate)borate LiODFB, and 0.4% lithium bis(oxalate)borate LiBOB.
[0078] (5) After standing for 8 hours, pre-forming is performed. The charging current is 0.05C, charging for 10 minutes, the charging current is 0.1C, charging for 20 minutes, and the charging current is 0.2C, charging for 30 minutes. After that, degas and sealing are performed. The formation format is:
[0079] a. Charge to 4.30V at 0.25C constant current and constant voltage;
[0080] b. Sleep for 30 minutes;
[0081] c. 0.5C discharge to 2.50V;
[0082] d. Repeat steps a to c twice;
[0083] e. 0.25C charging for 72 minutes.
[0084] (5) The battery in (4) was aged at 30±2°C for 7 days.
[0085] Embodiment 4:
[0086] (1) According to the weight percentage, the positive electrode slurry was prepared by mixing 84.8% nickel-cobalt-manganese 5 series ternary positive electrode + 10% lithium manganese iron phosphate (manganese iron molar ratio 6 / 4) + 3.4% positive electrode conductive agent (carbon black and carbon nanotubes) + 0.1% positive electrode dispersant YTF303 + 2.0% positive electrode binder PVDF. The positive electrode slurry with moderate solid content and viscosity was coated on the carbon-coated aluminum foil. The single-sided coating surface density of the positive electrode was 12.5 mg / cm 2 , then dried, rolled and cut, and temporarily stored for lamination.
[0087] (2) According to the weight percentage, the negative electrode slurry is prepared by mixing the active material graphite of 95% + the negative electrode conductive agent carbon black of 2.0% + the negative electrode dispersant CMC of 1.2% + the negative electrode binder styrene butadiene rubber formula. The positive electrode slurry with moderate solid content and viscosity is coated on the electrolytic copper foil. The negative electrode single-side coating surface density is 6.5 mg / cm 2 , then dried, rolled and sheared, and temporarily stored for lamination.
[0088] (3) The positive and negative electrodes and the 16 μm ceramic separator in (1) and (2) are stacked in the order of separator, negative electrode, separator, and positive electrode, wherein the positive electrode has 24 layers, the separator has 52 layers, and the negative electrode has 25 layers. The stacked electrode group is welded to the electrode tab, and then placed in a shell, sealed on the top and side, and dried.
[0089] (4) The batteries dried and qualified in (3) are injected with electrolyte at a rate of 4.0 g / Ah. The electrolyte comprises a lithium salt, a solvent and various additives, wherein the lithium salt is 11% lithium hexafluorophosphate LiPF6, 4.5% lithium bis(fluorosulfonyl)imide LiFSI, the solvent is 10% ethylene carbonate EC, 3% propylene carbonate PC, 20% ethyl methyl carbonate EMC, 45% ethyl propionate EP; the additives are 1.8% fluoroethylene carbonate FEC, 1.3% vinylene carbonate VC%, 1% vinyl sulfate DTD, 0.8% lithium difluorophosphate LiPO2F2 and 0.6% propylene sulfite PS, 0.4% lithium bis(fluorooxalate)borate LiODFB and 0.2% lithium bis(oxalate)borate LiBOB.
[0090] (5) After standing for 8 hours, pre-forming is performed. The charging current is 0.05C, charging for 10 minutes, the charging current is 0.1C, charging for 20 minutes, and the charging current is 0.2C, charging for 30 minutes. After that, degas and sealing are performed. The formation format is:
[0091] a. Charge to 4.30V at 0.25C constant current and constant voltage;
[0092] b. Sleep for 30 minutes;
[0093] c. 0.5C discharge to 2.50V;
[0094] d. Repeat steps a to c twice;
[0095] e. 0.25C charging for 72 minutes.
[0096] (5) The battery in (4) was aged at 30±2°C for 7 days.
[0097] Embodiment 5:
[0098] (1) According to the weight percentage, the positive electrode slurry is prepared by mixing 74.8% nickel-cobalt-manganese 6 series ternary positive electrode + 20% lithium manganese iron phosphate (manganese iron molar ratio 6 / 4) + 3.4% positive electrode conductive agent (carbon black and carbon nanotubes) + 0.1% positive electrode dispersant YTF303 + 2.0% positive electrode binder PVDF. The positive electrode slurry with moderate solid content and viscosity is coated on the carbon-coated aluminum foil. The single-sided coating surface density of the positive electrode is 12.5 mg / cm 2 , then dried, rolled and cut, and temporarily stored for lamination.
[0099] (2) According to the weight percentage, the negative electrode slurry is prepared by mixing the active material graphite of 95% + the negative electrode conductive agent carbon black of 2.0% + the negative electrode dispersant CMC of 1.2% + the negative electrode binder styrene butadiene rubber formula. The positive electrode slurry with moderate solid content and viscosity is coated on the electrolytic copper foil. The negative electrode single-side coating surface density is 6.5 mg / cm 2 , then dried, rolled and sheared, and temporarily stored for lamination.
[0100] (3) The positive and negative electrodes and the 16 μm ceramic separator in (1) and (2) are stacked in the order of separator, negative electrode, separator, and positive electrode, wherein the positive electrode has 34 layers, the separator has 72 layers, and the negative electrode has 35 layers. The stacked electrode group is welded to the tabs, and then placed in a shell, sealed on the top and side, and dried.
[0101] (4) The batteries dried and qualified in (3) are injected with electrolyte at a rate of 4.0 g / Ah. The electrolyte comprises a lithium salt, a solvent and various additives, wherein the lithium salt is 11% lithium hexafluorophosphate LiPF6, 4.5% lithium bis(fluorosulfonyl)imide LiFSI, the solvent is 10% ethylene carbonate EC, 3% propylene carbonate PC, 20% ethyl methyl carbonate EMC, 45% ethyl propionate EP; the additives are 1.8% fluoroethylene carbonate FEC, 1.3% vinylene carbonate VC%, 1% vinyl sulfate DTD, 0.8% lithium difluorophosphate LiPO2F2 and 0.6% propylene sulfite PS, 0.4% lithium bis(fluorooxalate)borate LiODFB and 0.2% lithium bis(oxalate)borate LiBOB.
[0102] (5) After standing for 8 hours, pre-forming is performed. The charging current is 0.05C, charging for 10 minutes, the charging current is 0.1C, charging for 20 minutes, and the charging current is 0.2C, charging for 30 minutes. After that, degas and sealing are performed. The formation format is:
[0103] a. Charge to 4.30V at 0.25C constant current and constant voltage;
[0104] b. Sleep for 30 minutes;
[0105] c. 0.5C discharge to 2.50V;
[0106] d. Repeat steps a to c twice;
[0107] e. 0.25C charging for 72 minutes.
[0108] (5) The battery in (4) was aged at 30±2°C for 7 days.
[0109] The detailed description of the high-power, high-specific energy, wide-temperature-range and high-safety lithium-ion battery and the preparation method thereof with reference to the above-mentioned embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
[0110] The battery of the implementation case was tested for high rate discharge, low temperature cold start, high temperature storage, overcharge and needle puncture safety performance. The test results are shown in Table 1.
[0111] Table 1 Comparison of battery performance in different embodiments
[0112]
[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium manganese iron phosphate battery with ultra-high power, high specific energy, wide temperature range and high safety, comprising a positive electrode sheet, a negative electrode sheet, a diaphragm, an electrolyte, an aluminum plastic shell and a tab, wherein the positive electrode sheet and the negative electrode sheet are respectively located on both sides of the diaphragm to form a laminated structure, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode mixture. The positive electrode current collector is a carbon-coated aluminum foil with a thickness of 8 to 12 μm. The positive electrode mixture includes a positive electrode active material, a positive electrode conductive agent, a positive electrode dispersant and a positive electrode binder. The positive electrode active material is a carbon-coated spherical nano-scale lithium manganese iron phosphate with a manganese / iron molar ratio of 6 / 4 or 7 / 3 and a particle size of 0.5 μm <D 50 <1.5μm, carbon coating layer 3~5nm; the negative electrode sheet includes a negative electrode current collector and a negative electrode mixture, the negative electrode mixture includes a negative electrode active material, a negative electrode conductive agent, a negative electrode dispersant and a negative electrode binder, the negative electrode active material adopts at least one of isotropic graphite, soft carbon, hard carbon, silicon carbon or silicon oxygen, and the particle size is 2μm<D 50 <6μm; the diaphragm adopts a ceramic-coated polyethylene diaphragm or a ceramic-coated polypropylene diaphragm with a thickness of 9 to 16μm; the electrolyte includes a lithium salt, a solvent and an additive, and the electrolyte conductivity at 25°C is above 10.5mS / cm.
2. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The positive electrode mixture comprises 95% to 95.6% of a positive electrode active material, 2.5% to 3% of a positive electrode conductor, 0.1% to 0.3% of a positive electrode dispersant and 1.5% to 2.0% of a positive electrode binder by weight percentage.
3. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The negative electrode mixture comprises, by weight percentage, 94.8% to 95.2% of a negative electrode active material, 2.0% to 3.0% of a negative electrode conductor, 0.7% to 1.5% of a negative electrode dispersant and 1.5% to 2.5% of a negative electrode binder.
4. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The lithium salt in the electrolyte is at least two of lithium bis(fluorosulfonyl)imide LiFSI, lithium hexafluorophosphate LiPF6 and lithium bis(trifluoromethylsulfonyl)imide LiTFSI, with a mass concentration of 11% to 22%; the solvent is at least two of vinyl carbonate EC, ethyl methyl carbonate EMC, propylene carbonate PC, ethyl propionate EP, methyl propionate MP and diethyl carbonate DEC, with a mass concentration of 72% to 82%; the additives include at least four of vinyl carbonate VC, propylene sulfite PS, fluoroethylene carbonate FEC, vinyl sulfate DTD, lithium difluorophosphate LiPO2F2, lithium tetrafluoroborate LiBF4, lithium bis(fluorooxalate)borate LiODFB and lithium bis(oxalate)borate LiBOB, with a mass concentration of 5% to 10%.
5. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The positive electrode current collector is a carbon-coated aluminum foil, wherein the base foil thickness is 7-10 μm and the carbon-coated layer thickness is 1-2 μm; the negative electrode current collector is an electrolytic copper foil, wherein the thickness of the electrolytic copper foil is 4.5-8 μm.
6. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1 or 2, characterized in that: The positive electrode conductive agent is at least one of carbon black, Ketjen black or carbon nanotubes, the dispersant is at least one of polyvinyl pyrrolidone and polydiphenyl butylene ester, and the positive electrode binder is polyvinylidene fluoride.
7. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The positive electrode sheet is coated on both sides, wherein the single-side coating density of the positive electrode mixture is 7.1 to 12.5 mg / cm 2 The negative electrode sheet is coated on both sides, and the single-sided coating density of the negative electrode mixture is 3.6 to 7.2 mg / cm 2 .
8. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1 or 3, characterized in that: The negative electrode conductive agent is at least one of graphene, carbon black, Ketjen black or carbon nanotubes, the negative electrode dispersant is sodium carboxymethyl cellulose CMC, and the negative electrode binder is styrene-butadiene rubber SBR.
9. The ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to claim 1, characterized in that: The thickness of the aluminum-plastic shell is 0.113-0.153 mm, the size of the positive electrode tab is 25-60 mm wide and 0.3-0.4 mm thick, and the size of the negative electrode tab is 25-60 mm wide and 0.2-0.3 mm thick.
10. The method for preparing the ultra-high power, high specific energy, wide temperature range and high safety lithium manganese iron phosphate battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) The positive electrode active material, conductive agent, binder and dispersant are made into a uniform and stable slurry according to the homogenization process, the slurry is coated on the positive electrode collector, dried at a certain temperature and wind speed, and then rolled before entering the subsequent process; the negative electrode active material, conductive agent, binder and dispersant are made into a uniform and stable slurry according to the homogenization process, the slurry is coated on the negative electrode collector, dried at a certain temperature and wind speed, and stored before entering the next process; 2) Cut the rolled positive and negative electrode sheets into a certain width respectively, and stack them together in the order of separator, negative electrode sheet, separator, and positive electrode sheet to form a stacked electrode group, which is then short-circuited and X-ray aligned; 3) The qualified pole group and the pole ear are welded together, loaded into an aluminum plastic shell, and pre-packaged on the top in turn. After the packaging effect is checked, the qualified battery cell enters a vacuum high-temperature oven for several hours to remove the trace moisture remaining in the battery. The drying temperature is 80-95°C, the drying time is 24-36 hours, and the vacuum degree is -100kPa; 4) Perform a short circuit test on the dried battery, and test the moisture content of the positive electrode, negative electrode and diaphragm respectively; inject a certain amount of electrolyte into the battery with qualified moisture, with a net liquid volume of 4.2-5.3 mg / Ah, and let it stand for 4-12 hours; 5) After the standing is completed, the pre-formation is performed first, and the battery is activated by charging with a small rate current, the charging current is 0.05C-0.2C, and the charging time is 30-60 minutes. At the same time, the gas generated during the battery activation process is discharged to form a compact and uniform solid electrolyte membrane; 6) After pre-forming, exhaust, sealing and forming are carried out. Formation process: the battery is charged and discharged 1 to 3 times to fully activate it. The charge and discharge current is 0.2C to 0.5C, and the charge and discharge voltage is 2.5 to 4.3V; 7) After the formation, the aging process begins. The aging temperature is 35-40°C and the aging time is 7-10 days.
Citation Information
Patent Citations
Lithium manganese iron phosphate battery with high safety and high energy density
CN117276471A
Lithium manganese iron phosphate battery electrolyte and battery thereof
CN117691183A
High-dispersion slurry mixing process for lithium iron manganese phosphate battery
CN117855426A
Cited By
High-magnification long-life energy storage monomer, battery device, power utilization device and energy storage device
CN121439880A
A high-rate long-life energy storage cell, a battery device, a power utilization device, and an energy storage device
CN121439880B